TRPM4 cation channel mediates axonal and neuronal degeneration in experimental autoimmune encephalomyelitis and multiple sclerosis - Schattling, Benjamin; Freichel, Marc (Nature medicine, 2012)
In multiple sclerosis, an inflammatory disease of the central nervous system (CNS), axonal and neuronal loss are major causes for irreversible neurological disability. However, which molecules contribute to axonal and neuronal injury under inflammatory conditions remains largely unknown. Here we show that the transient receptor potential melastatin 4 (TRPM4) cation channel is crucial in this process. TRPM4 is expressed in mouse and human neuronal somata, but it is also expressed in axons in inflammatory CNS lesions in experimental autoimmune encephalomyelitis (EAE) in mice and in human multiple sclerosis tissue. Deficiency or pharmacological inhibition of TRPM4 using the antidiabetic drug glibenclamide resulted in reduced axonal and neuronal degeneration and attenuated clinical disease scores in EAE, but this occurred without altering EAE-relevant immune function. Furthermore, Trpm4−/− mouse neurons were protected against inflammatory effector mechanisms such as excitotoxic stress and energy deficiency in vitro. Electrophysiological recordings revealed TRPM4-dependent neuronal ion influx and oncotic cell swelling upon excitotoxic stimulation. Therefore, interference with TRPM4 could translate into a new neuroprotective treatment strategy
Gesehen am 16.04.2018